Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine which lines are perpendicular to the line [tex]\( y - 1 = \frac{1}{3}(x + 2) \)[/tex], we need to find the slope of the given line and then identify the slopes of the other lines given in the question.
1. Find the slope of the given line:
The given line is:
[tex]\[ y - 1 = \frac{1}{3}(x + 2) \][/tex]
We can rewrite this equation in slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y - 1 = \frac{1}{3}x + \frac{1}{3}(2) \][/tex]
[tex]\[ y - 1 = \frac{1}{3}x + \frac{2}{3} \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{2}{3} + 1 \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{5}{3} \][/tex]
The slope of the given line is [tex]\( \frac{1}{3} \)[/tex].
2. Determine the slope of a line perpendicular to the given line:
For two lines to be perpendicular, the product of their slopes must be [tex]\(-1\)[/tex]. Thus, the slope of the perpendicular line should be the negative reciprocal of [tex]\( \frac{1}{3} \)[/tex], which is [tex]\( -3 \)[/tex].
3. Check each given line to see if its slope is [tex]\( -3 \)[/tex]:
- For the line [tex]\( y + 2 = -3(x - 4) \)[/tex]:
[tex]\[ y + 2 = -3(x - 4) \][/tex]
Simplifying, we get:
[tex]\[ y + 2 = -3x + 12 \][/tex]
[tex]\[ y = -3x + 10 \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. Since this matches the slope required for perpendicularity, this line is perpendicular.
- For the line [tex]\( y - 5 = 3(x + 11) \)[/tex]:
[tex]\[ y - 5 = 3(x + 11) \][/tex]
Simplifying, we get:
[tex]\[ y - 5 = 3x + 33 \][/tex]
[tex]\[ y = 3x + 38 \][/tex]
The slope of this line is [tex]\( 3 \)[/tex]. Therefore, this line is not perpendicular.
- For the line [tex]\( y = -3x - \frac{5}{3} \)[/tex]:
[tex]\[ y = -3x - \frac{5}{3} \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. This matches the required slope for perpendicularity, so this line is perpendicular.
- For the line [tex]\( y = \frac{1}{3}x - 2 \)[/tex]:
[tex]\[ y = \frac{1}{3}x - 2 \][/tex]
The slope of this line is [tex]\( \frac{1}{3} \)[/tex]. This does not match the required slope for perpendicularity, so this line is not perpendicular.
- For the line [tex]\( 3x + y = 7 \)[/tex]:
[tex]\[ 3x + y = 7 \][/tex]
Rearranging to slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y = -3x + 7 \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. This matches the required slope for perpendicularity, so this line is perpendicular.
Thus, the lines that are perpendicular to [tex]\( y - 1 = \frac{1}{3}(x + 2) \)[/tex] are:
1. [tex]\( y + 2 = -3(x - 4) \)[/tex]
2. [tex]\( y = -3x - \frac{5}{3} \)[/tex]
3. [tex]\( 3x + y = 7 \)[/tex]
The correct lines are [tex]\( 1, 3,\)[/tex] and [tex]\( 5 \)[/tex].
1. Find the slope of the given line:
The given line is:
[tex]\[ y - 1 = \frac{1}{3}(x + 2) \][/tex]
We can rewrite this equation in slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y - 1 = \frac{1}{3}x + \frac{1}{3}(2) \][/tex]
[tex]\[ y - 1 = \frac{1}{3}x + \frac{2}{3} \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{2}{3} + 1 \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{5}{3} \][/tex]
The slope of the given line is [tex]\( \frac{1}{3} \)[/tex].
2. Determine the slope of a line perpendicular to the given line:
For two lines to be perpendicular, the product of their slopes must be [tex]\(-1\)[/tex]. Thus, the slope of the perpendicular line should be the negative reciprocal of [tex]\( \frac{1}{3} \)[/tex], which is [tex]\( -3 \)[/tex].
3. Check each given line to see if its slope is [tex]\( -3 \)[/tex]:
- For the line [tex]\( y + 2 = -3(x - 4) \)[/tex]:
[tex]\[ y + 2 = -3(x - 4) \][/tex]
Simplifying, we get:
[tex]\[ y + 2 = -3x + 12 \][/tex]
[tex]\[ y = -3x + 10 \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. Since this matches the slope required for perpendicularity, this line is perpendicular.
- For the line [tex]\( y - 5 = 3(x + 11) \)[/tex]:
[tex]\[ y - 5 = 3(x + 11) \][/tex]
Simplifying, we get:
[tex]\[ y - 5 = 3x + 33 \][/tex]
[tex]\[ y = 3x + 38 \][/tex]
The slope of this line is [tex]\( 3 \)[/tex]. Therefore, this line is not perpendicular.
- For the line [tex]\( y = -3x - \frac{5}{3} \)[/tex]:
[tex]\[ y = -3x - \frac{5}{3} \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. This matches the required slope for perpendicularity, so this line is perpendicular.
- For the line [tex]\( y = \frac{1}{3}x - 2 \)[/tex]:
[tex]\[ y = \frac{1}{3}x - 2 \][/tex]
The slope of this line is [tex]\( \frac{1}{3} \)[/tex]. This does not match the required slope for perpendicularity, so this line is not perpendicular.
- For the line [tex]\( 3x + y = 7 \)[/tex]:
[tex]\[ 3x + y = 7 \][/tex]
Rearranging to slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y = -3x + 7 \][/tex]
The slope of this line is [tex]\( -3 \)[/tex]. This matches the required slope for perpendicularity, so this line is perpendicular.
Thus, the lines that are perpendicular to [tex]\( y - 1 = \frac{1}{3}(x + 2) \)[/tex] are:
1. [tex]\( y + 2 = -3(x - 4) \)[/tex]
2. [tex]\( y = -3x - \frac{5}{3} \)[/tex]
3. [tex]\( 3x + y = 7 \)[/tex]
The correct lines are [tex]\( 1, 3,\)[/tex] and [tex]\( 5 \)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.